Strategi Produksi Low-Budget: Peran Produser dalam Menjaga Production Value Film Pendek Perahu (2024) - Ishmaturrahman, Fikri; Sitepu, Petrus Damiami (Universitas Bunda Mulia, 2025)
This study discusses the strategic role of the producer in maintaining Production Value in the short film Perahu (2024), which was produced on a limited budget production, particularly within the context of independent film production by amateurs and students. In the filmmaking process, a producer plays a critical role in designing strategies that balance time (fast), cost (cheap), and quality (good) to achieve optimal results. This research employs a descriptive qualitative method using a case study approach to explore in depth the production practices applied, with a primary focus on the pre-production stage, especially the casting and location scouting processes. Open casting was conducted through social media as a cost-effective strategy to attract potential actors at minimal expense. Meanwhile, location scouting was carried out in a structured manner, taking into account technical feasibility, visual aesthetics, and budget flexibility. The results indicate that the success in maintaining Production Value is not solely determined by the amount of funding but also by careful time management, optimal use of available resources, and the producer’s ability to adapt and negotiate effectively. These findings demonstrate that low-budget short films can still achieve broadcast-quality results when supported by well-measured production strategies initiated in the pre-production phase. This study not only contributes to the development of academic literature in the field of film production management but also serves as a practical reference for emerging filmmakers or students seeking to produce high-quality visual works despite limited resources.